Wychowanie chrześcijańskie w świetle literatury i dokumentów Kościoła u progu trzeciego tysiąclecia - perspektywy rozwojowe - Danuta Wajsprych (Nicolaus Copernicus University in Toruń, 2009)
Nowadays the role of Christian pedagogy in the formation of the man's identity as   an individual in the community of social life is not the subject of wider discussions. It   seems to be indispensable not only in regard of the tradition and the past, but mostly in regard of the present and the future. The man it in day of informative technology, active   civilization changes, which are always followed by the necessity of solving the problems   of existential nature, needs constant and solid references and permanent values which   will enable his full personal development. Just there, Christian conception of education,   in centre of which stand man as a person (conscious and free subject) together with his   integral development, can play the main role.   In the light of the above, the intention of this article is to show the chances possibilities   of Christian education against a background of literature and the documents of   the Church at the threshold third millennium. However, the main aim of it is to answer   the question why it is worth and even necessary to draw an inspiration in the Christian  education.